Orangutans not Infected with Plasmodium vivax or P. cynomolgi, Indonesia - Balbir, Singh; Paul C, Divis (NationalCenter for Biotechnology Information, U.S. National Library of Medicine, 2009)
After orangutans in Indonesia were reported as infected with Plasmodium cynomolgi and P. vivax, we conducted phylogenetic analyses of small subunit ribosomal RNA gene sequences of Plasmodium spp. We found that these orangutans are not hosts of P. cynomolgi and P. vivax. Analysis of >1 genes is needed to identify Plasmodium spp. infecting orangutans.